The Irish in Quebec: An Introduction to the Historiography - Gossage, Peter (Labour / Le Travail, 1995)
The article reviews the book, "The Irish in Quebec: An Introduction to the Historiography," by Robert J. Grace.
Keywords: BOOKS – Reviews; GRACE; Robert J.; Historiography; IRISH in Quebec: An Introduction to the Historiography; The (Book); Nonfiction